Redefining Sustainability Reporting: The Interplay Between Stakeholder Engagement, Accountability and Organisational Performance of Public Entities - Anyass Ahmed Ibrahim (East African Journal of Business and Economics, 2026)
Purpose: Researchers have emphasised the necessity for public entities to engage in sustainability reporting, similar to corporate entities. The current study uses stakeholder engagement to understand how sustainability performance ensures accountability and organisational performance within the operations of public entities in developing nations. This is predicated on the critical role public entities play in relation to the need to ensure accountability through sustainability reporting in the public sector. A conceptual model was developed to assist in achieving the objective of the study. Design/Methodology/Approach: Data were collected from 70 respondents utilising a survey instrument. Analysis was conducted through descriptive statistics to meet the objective of the study. Findings: The study highlights the crucial role of stakeholder engagement in the success of sustainability reporting, which in turn fosters accountability and enhances the organisational performance of public entities. Research Limitation: The study is confined to the public sector and employs a survey approach to reexamine sustainability reporting as a means of ensuring accountability within the context of stakeholder engagement. Practical Implication: The significant role of stakeholders as drivers of sustainability underscores the need for stakeholder engagement in sustainability reporting, thereby exerting accountability in this area. Social Implication: It is advisable that policymakers and regulators seeking to achieve organisational performance and ensure accountability should involve stakeholders in sustainability reporting and developing sustainable programs. The absence of stakeholder engagement could have consequences for sustainability reporting and sustainable programs. Originality and Value: The new insight of the study is the reconstruction of the narrative around sustainability reporting, thus emphasising its deployment as an accountability and performance measurement mechanism.